EFEKTIVITAS PKB TERINTEGRASI (PUBLIKASI ILMIAH, KARYA INOVATIF, KOMUNITAS BELAJAR) TERHADAP KINERJA GURU DI SDN BANJARKEJEN PANDAAN - Wanda Sulaksono; Suyanto Suyanto; A. Faizin (STKIP Pesisir Selatan, 2026)
Objective: This study aims to analyze the effectiveness of an integrated Continuous Professional Development (PKB) program which consists of scientific publication, instructional innovation, and professional learning communities in improving teacher performance at SDN Banjarkejen Pandaan. Using a qualitative design, the study employed observation, in-depth interviews, and documentation to explore teachers’ and school leaders’ experiences, perceptions, and professional practices. Thematic analysis was applied to identify patterns, meanings, and interrelations across PKB components within the framework of educational quality management. The findings indicate that scientific publication enhances teachers’ academic reflection by encouraging data-driven evaluation of instructional practices. Instructional innovation contributes to pedagogical adaptation, improving student engagement and classroom management effectiveness. Professional learning communities serve as collaborative spaces that support peer supervision, instructional dialogue, and collective improvement of practice. This study concludes that the effectiveness of PKB lies in the synergy among reflection, creativity, and collaboration. Practical implications highlight the need for structured mentoring in academic writing, strengthened documentation of instructional innovations, and consistent management of learning communities